Depression and rising incidents of suicide among undergraduates in Nigeria: A survey of Southeast - Emeka Michael, Onwuama; Emmanuel J., Ibuot,; Christian, Agbo,; Aloysius, Obiwulu, (International Journal of Psychosocial Rehabilitation, 2024)
Background:Depression, and suicide experiences are prevailing in Nigerian higher institutions of learning. The need to find out their primary causes necessitated this study. Aims/Objectives: The aims were to investigate the primary factors responsible for depression; and the relationship between the depression and rising incidents of suicide among undergraduates in Southeast Nigerian universities. Methods: A cross-sectional survey wherein structured questionnaire was used to generate data in 10 public universities was adopted. From a population of 79,751 students, 398 was adopted as sample using Guilford and Flruchter (1973) formula for estimating sample size, while tables, percentage and the Statistical Package for the Social Sciences (SPSS version 20.0) tools were used to dataanalyse. Results: The results reveal among others that lack of appropriate transportation and accommodation systems; financial brokenness, imposition of textbooks/hand-outs and compulsory sorting, disruption of academic activities; congested academic activities, and incompetency/poor academic performance are the major causes of depression among undergraduates. It further reveals that hopeless,examination failure and major disappointments, which cause depression, lead to suicide among undergraduates in Southeast Nigeria. Conclusions: Depression is inevitable among undergraduates and has a significant relationship with the rising incidents of suicide in tertiary institutions in the Southeast.